THE LAWS ON “SIRRI MARRIED AND INTS IMPACT - Sahal Afhami; Anis Mashdurohatun (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Marriage is legal if it is done according to the Law on Religion and belief respectively and in order to have legal force and apply the power of the marriage must be registered. Reality is happening in the society there is a practice often seen Sirri marriage lawful religion, but does not have the force of law according to the positive effect. This study aims ffor know how the views of Islamic law and positive law in marriage Sirri, the factors that cause it, and how the process of completion according to the positive law. This research is normaif law, the research data source is the secondary law, both secondary-primary, and secondary-sekuder and secondary-tertiary. The tools used in the form of study documents, and the deductive and inductive analysis in descriptive form. The findings generated in this study are: (1) the grounds of marriage Sirri menur ut Islamic law is valid, but according to the positive law of marriage does not have the force valid as evidence to ensure legal certainty. (2) the factors that lead to marriage Sirri was done because of lack of knowledge and awareness of the law that the marriage should be registered. (3) the process of completion once the divorce judgment to become one. Keywords: impact, marriage Sirri, positive law.